Beads from excavations at Qustul, Adindan, Serra East, Dorginarti, Ballana and Kalabsha - Then-Obłuska, Joanna, (University of Chicago Oriental Institute Nubian Expedition (Series) ;, 2022)
This book presents a comprehensive corpus of beads and pendants found during excavations undertaken by the Oriental Institute of the University of Chicago between 1960 and 1968 at the Lower Nubian sites of Qustul, Adindan, Serra East, Dorginarti, Ballana and Kalabsha and stored in the Oriental Institute Museum.